Recent advances on the mechanism of acupuncture in the treatment of subjective tinnitus - Shi, Feifei; Ye, Ziyu; Zha, Bixiang; Wu, Weixian; Zhang, Yating; Yu, Leiyu; Liu, Wanting; Rong, Yan; Yang, Jun (Frontiers in Systems Neuroscience, 2025)
ObjectiveTo review and organize the research results on the mechanism of action of acupuncture in the treatment of subjective tinnitus over the past 30 years. This will provide a reference basis for the clinical acupuncture treatment of subjective tinnitus.MethodsComputer searches of PubMed, China National Knowledge Infrastructure (CNKI), and China Science and Technology Journal Database (CCD) were conducted to collect and organize literature on the research on the mechanism of action of acupuncture in the treatment of subjective tinnitus. The searches were limited to the period from January 1, 1995 to July 31, 2024. The literature was then summarized and analyzed in terms of the blood circulation of the inner ear, immuno-inflammation, and neural cells to elaborate on the potential mechanism of action of acupuncture. The objective of this study was to describe the potential mechanism of action of acupuncture. The final results yielded 36 research papers related to subjective tinnitus and the mechanism of action of acupuncture. The identified mechanisms are as follows: the enhancement of local microcirculation in the inner ear by regulating the blood supply of the vertebrobasilar artery may improve the inner ear’s blood supply obstacle. Additionally, the reduction of immuno-inflammatory factors in the inner ear may reduce the toxicity of the cochlea’s hair cells and protect them. The modulation of 5-hydroxytryptamine receptors in the cochlear nucleus may serve to protect spiral ganglion neurons from damage. Additionally, the modulation of the thalamus and the functional reorganization of the auditory cortex and synaptic network may contribute to the achievement of therapeutic effects.ConclusionWhile acupuncture has demonstrated clinical efficacy in the treatment of subjective tinnitus, the underlying mechanism of action remains poorly understood. In the future, there is a need to accelerate the application of modern advanced technology and multidisciplinary cross-fertilization, as well as to conduct in-depth and systematic investigations into the mechanisms of acupuncture effects. This will provide an objective basis for clinical treatment.